Anti-corruption management in the health care system: the legal aspect - М. А. Anishchenko (Zaporozhye State Medical University, 2019)
The purpose of the research. To analyze the concept of anti-corruption management and organizational and legal aspects of the implementation of anti-corruption activities in health care institutions, on the basis of the analyzed material, to define the concept of "anti-corruption management in health care institutions", to determine legal problems in the organization of the indicated activity and to outline ways of their solution. Materials and methods. The research material is the current normative legal acts and normative documents regulating the implementation of anti-corruption activities in health care institutions. Structural-functional and system-analytical methods, method of information search and generalization were used. Results. Analyzing the current legal acts, anti-corruption management includes the following main areas of activity (functions): determination of the person (unit) responsible for preventing and detecting corruption in the health care establishment and creating the necessary conditions for its (her) successful work; development and approval of the necessary internal documents on issues of anti-corruption activities, their constant and timely updating; implementation of anti-corruption legislation in other internal documents of the health care institution; realization of corruption risk assessment; ensuring proper prevention and conflict resolution of interests; ensuring openness and transparency of the health care institution's activities; organization of anti-corruption education of employees of the institution of health care; the proper management of information on corruption offenses; maintenance of the necessary registers and databases; control and monitoring of the effectiveness of anti-corruption measures. Conclusions. Thus, the anti-corruption management of healthcare institutions is a type of organizational and managerial activity of managers, founders and authorized persons (departments) of healthcare institutions of all forms of ownership, based on legal norms, aimed at creating and operating an effective system of preventing and combating corruption in healthcare institutions, as well as control the effectiveness of anti-corruption measures. Some legal aspects of anti-corruption management require serious improvement.